Pengaruh Penerapan Manajemen Risiko Terhadap Kinerja Keuangan Perbankan Yang Terdaftar di Bursa Efek Indonesia 2021- 2024 - Rahman, Rahman; Aisyah , Sitti; Amir, Amir (Pusat Riset dan Inovasi Nasional, 2026)
This quantitative study aims to analyze the effect of risk management implementation on the financial performance of banks listed on the Indonesia Stock Exchange. The sample was taken from the official website of the Indonesia Stock Exchange. The data used in this study is quantitative, obtained through analysis of financial statements and annual reports of banks listed on the Indonesia Stock Exchange. Data collection was carried out to ensure the accuracy and completeness of the information used for analysis. In this study, the data source used in data collection was secondary data. Based on the results of the data research using statistical calculations through the Statistical Package for the Social Science (SPSS) application regarding the effect of risk management implementation on the financial performance of banks listed on the Indonesia Stock Exchange (IDX) for the 2021-2024 period, as discussed in the previous chapter, the author concludes that the importance of implementing overall risk management, including credit risk, market risk, liquidity risk, and operational risk, significantly impacts financial performance indicators, namely ROA, ROE, and NIM. The implementation of risk management must be further improved and maintained, as the research results indicate that the existing risk management implementation remains quite stable.